Surgical treatment of tubal ectopic pregnancy through posterior colpotomy: experience from a Brazilian university hospital - Tábata Longo da Silva Machado; Alysson Zanatta; Larissa Gonçalves Braz Santos; Rafaella Ferreira de Araújo Litvin; Lizandra Moura Paravidine Sasaki; Júlio Elito Júnior; Edward Araujo Júnior; Alberto Moreno Zaconeta (Korean Society of Obstetrics and Gynecology, 2019)
The objective of this study was to evaluate the feasibility of posterior colpotomy for the surgical treatment of tubal ectopic pregnancy in hemodynamically stable women. We performed a retrospective analysis of medical records obtained over a period of 18 months. Twelve cases were identified, with the following characteristics: mean gestational age, 7.7 weeks; mean serum β-human chorionic gonadotropin level, 7,786 mIU/mL; and greater diameter of the mass, 15-69 mm. Treatment was successful in all cases. Salpingectomy was performed in 10 patients (83.3%) and salpingostomy, in 1 patient. The remaining patient only received peritoneal lavage, as the evidence of ectopic abortion with only a slightly dilated uterine tube was found during surgery. The mean surgical time was 42.5 minutes. In the analyzed cases, posterior colpotomy was found to be a feasible alternative method for the surgical treatment of tubal ectopic pregnancy in hemodynamically stable women.